MODEL PELAKSANAAN BIMBINGAN DAN KONSELING KOMPREHENSIF SEKOLAH DASAR DI SD MUHAMMADIYAH PROGRAM KHUSUS KOTA SURAKARTA - Minsih Minsih (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
SD Muhammadiyah Surakarta Special Program one of the elementary school students whostrive to be perfect man to deliver. The purpose of this study in the first year is to describe aconceptual model of the ideal implementation of comprehensive guidance and counseling services inSD Muhammadiyah Surakarta and Special Programs in the second year to describe theimplementation process of comprehensive services BK is the basic guidance services, Responshipservices, individualized service planning, and support system implemented in SD MuhammadiyahSurakarta Special Programs. This study is a qualitative study with a phenomenological approachnaturalistic. Phenomenological approach seeks to understand human behavior in terms of aframework of thinking and acting people themselves. Guidance and counseling serviceskomprehensif held in SD Muhammadiyah Surakarta Special Program is a companion program that isintended for all students under the guidance of psychologists and counselors. This service consists ofseveral activities, namely basic guidance services, responsive services and service planning guidanceis individual.Layanan basic services provided to all students in order to achieve optimal process ofself development through activities classically presented systematically. This service also aims toprevent the onset of problems in the educational process in schools. The responsive service is aservice provided to students who have problems and special needs that require separate handling.